2003
DOI: 10.1016/j.cogdev.2003.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Historical change, cultural learning, and cognitive representation in Zinacantec Maya children

Abstract: Against the background of an unchanging sequence of representational development, we demonstrate that implicit processes of learning and cognition can change from one historical period to another. One generation of Zinacantec Maya children was studied in 1969 and 1970, the next generation in 1991 and 1993. In the intervening two decades, the community, located in Chiapas, Mexico, was involved in a transition from an economy based primarily on subsistence and agriculture to an economy based primarily on money a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 14 publications
(13 reference statements)
4
93
0
3
Order By: Relevance
“…A recent longitudinal study in Zinantec Mayan communities in Chiapas, Mexico find that, over a period of 30 years, a shift from agricultural subsistence to entrepreneurial commerce was associated with a change from a conservative weaving apprenticeship (emphasizing compliance to the master) to an innovative apprenticeship (featured by learner independence and experimentation) (Greenfield et al 2003). Moreover, this change in social organization was associated with a shift from concrete to abstract representation of weaving patterns.…”
Section: Production Of Independent and Interdependent Values And Pracmentioning
confidence: 99%
“…A recent longitudinal study in Zinantec Mayan communities in Chiapas, Mexico find that, over a period of 30 years, a shift from agricultural subsistence to entrepreneurial commerce was associated with a change from a conservative weaving apprenticeship (emphasizing compliance to the master) to an innovative apprenticeship (featured by learner independence and experimentation) (Greenfield et al 2003). Moreover, this change in social organization was associated with a shift from concrete to abstract representation of weaving patterns.…”
Section: Production Of Independent and Interdependent Values And Pracmentioning
confidence: 99%
“…Research has shown that socioeconomic development predicts various indicators of individualism, independence and autonomy, both contemporaneously across nations and historically within nations (Greenfield, 2013;Greenfield, Maynard, & Childs, 2003;Grossmann & Varnum, 2015;Hofstede, 2001;Inglehart & Baker, 2000;H. Park, Twenge, & Greenfield, 2014).…”
Section: Study 2d: Models Of Selfhood In Ecocultural Contextmentioning
confidence: 99%
“…Goodnow, 2001). As Greenfield, Maynard, and Childs (2003) have put it, "In sum, socialization and development are not fixed but adapt, in a coordinated way, to changing ecological conditions" (p. 455).…”
Section: Parental Ethnotheories and The Child's Learning Environmentmentioning
confidence: 99%